HUMAN RESOURCES AS A FACTOR OF PROVIDING UKRAINE SOCIAL SECURITY SYSTEM IN MODERN CONDITIONS - Stavnycha, N. I. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2019)
The purpose of the article is to research and analyze indicators that directly effect on the level of country’s human resources development, and assessment of Ukraine’s rating place among other countries. The following methods of scientific research, such as generalization, comparison and analysis were used to achieve the goal. The attention is focused on the fact that in conditions of post-industrial economy, the role of human and its knowledge increase, resulting in implementing the human development concept. This concept is aimed at forming measures to prevent the population impoverishment, unemployment, loss of health by stimulating human development, increasing its role in society, and, at the same time, increasing responsibility to society. The main task of the concept is to ensure the welfare of the person. The article shows the comparative assessment of Ukraine’s ranking among other countries according to the human development index and its components. The following indicators such as gross national income per capita, average and expected duration of training, average life expectancy at birth were analyzed. It was agreed that economic ability to create and use human resources to a greater extent determines human well-being and is the main criteria for assessing the social security level. Since the background for well-being is income, education, and human health, social security becomes an integrating link between the modern concept of human development and the state social policy. In this manner, everything that reduces welfare, harms a particular person and society as a whole are factors that threaten social security. In this context human resources emerged as a key resource to the state development.